2005
DOI: 10.1111/j.1365-2745.2005.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall, land use and woody vegetation cover change in semi-arid Australian savanna

Abstract: Summary 1The relative roles of climate and management for driving changes in woody cover in savannas over the past century are the subject of active debate. Perspectives arising from short-term, small-scale, local experiments are rarely tested over larger scales and longer time frames. 2 Regression analysis and aerial photography were used to assess the relative importance of land-use history (fire and grazing), rainfall and initial woody cover (woody cover at the beginning of a sample period relative to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
225
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 250 publications
(242 citation statements)
references
References 56 publications
12
225
0
5
Order By: Relevance
“…Encroachment of woody vegetation into grassland communities and the resultant conversion of these communities into closed canopy forests is an increasingly common phenomenon (Archer 1989;Van Auken 2000;Peterson and Reich 2001;Roques et al 2001;Silva et al 2001;Fensham et al 2005), and grassland-dominated landscapes are increasingly rare globally (Hoekstra et al 2004). Species compositional shifts caused by woody encroachment into grasslands have important implications for community dynamics and ecosystem properties, such as carbon (C) storage and nitrogen (N) cycling (Post et al 1982;Reich et al 2001b;Jackson et al 2002;McCulley et al 2004;Knapp et al 2008;McKinley and Blair 2008;Barger et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Encroachment of woody vegetation into grassland communities and the resultant conversion of these communities into closed canopy forests is an increasingly common phenomenon (Archer 1989;Van Auken 2000;Peterson and Reich 2001;Roques et al 2001;Silva et al 2001;Fensham et al 2005), and grassland-dominated landscapes are increasingly rare globally (Hoekstra et al 2004). Species compositional shifts caused by woody encroachment into grasslands have important implications for community dynamics and ecosystem properties, such as carbon (C) storage and nitrogen (N) cycling (Post et al 1982;Reich et al 2001b;Jackson et al 2002;McCulley et al 2004;Knapp et al 2008;McKinley and Blair 2008;Barger et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Decline and elimination of plant populations whose seed production is interrupted by frequent fires have been documented in a wide range of fire-prone habitats (Fox and Fox 1986; Nieuwenhuisfrequent to allow height development beyond scorch height (Hoffmann 1998;Hoffmann and Solbrig 2003). Species that produce lignotuberous seedlings are more resistant to repeated burning than obligate seeders but may decline over a long period of frequent fire if repeated defoliation depletes starch reserves or if seedlings die before they can develop a lignotuber (Bowen and Pate 1993;Walters et al 2005;Fensham and Fairfax 2006). Seemingly low annual rates of fire-induced mortality may lead to considerable changes in population densities when compounded over many years of frequent burning.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, long-term (34-55 years) repeated burning is expected to change the composition and density of non-herbaceous plants in the understorey, resulting in a simplification of vegetation structure (Spencer and Baxter 2006;Fairfax et al 2009). Temporal changes in woody plant communities will also be affected by fluctuations in environmental factors other than fire (Bradstock et al 1997;Sharp and Bowman 2004;Fensham et al 2005), such that it is important to consider the effects of other environmental influences.…”
Section: Introductionmentioning
confidence: 99%
“…Studies based on remote-sensing methods have shown periods of relatively high vegetation cover since ca. 1950: in the dune fields of Burkina Faso, which is located in the southwestern Sahara Desert, this period occurred in the late 1990s [81]; it occurred from the 1950s to the mid-1960s in northeastern Australia [82] and from the mid-1980s to the early 1990s in the southwestern United States [83]. In each of these regions, the periods with higher vegetation cover were associated with lower dune activity.…”
Section: Advances In Current Research On Sandy Desertificationmentioning
confidence: 99%